Effect of online aerobic exercise training in patients with bipolar depression: Protocol of a randomized clinical trial - Wang, Xueqian; Luo, Huirong; Zhang, Yinlin; Mao, Maolin; Lu, Yulin; Zhang, Zheng; Jiang, Chunfeng; Luo, Qinghua (Frontiers in Psychiatry, 2022)
Introduction: Bipolar disorder (BD) is a common and debilitating mental illness that affects about 400 million people worldwide, decreasing their functionality and quality of life. Medication and psychotherapy are recommended for treatment of BD, while some evidence indicates that exercise could improve the clinical outcome of BD. This study aims to investigate whether exercise intervention could reduce the mood symptoms and inflammation level of BD.Methods: This is a longitudinal,, interventional, randomized, single-blind trial. We plan to recruit 94 patients diagnosed with BD in depression episode. Patients will be randomly assigned to treatment as usual + aerobic exercise group (intervention group) and treatment as usual (TAU) only group, at a ratio of 1:1. The intervention group will undergo 40-min aerobic exercise training twice a week for eight weeks. The primary outcome of this study is the mean change of Hamilton Depression Rating Scale 17 (HAMD 17) scores from baseline to week 8. The Young Manic Rating Scale (YMRS), Self-Rating Depression Scale (SDS), and Interleukin-6 (IL-6), Tumor necrosis factor-α（TNF-α) and C-reactive protein (CRP) levels will also be measured. The measurements will be performed at baseline, immediately after intervention and two months after intervention. Discussion: Aerobic exercise training + treatment is expected to bring more benefits to BD patients than TAU only. This trial might provide stronger evidence of physical exercise efficacy for BD treatment.Clinical Trial Registration: This study was approved by the Chinese Clinical Trial Registry (Registration Code: ChiCTR2200057159). Registered on 1 March 2022.